The Impact of the Tourism Industry on Local Revenue in Langsa City - Muhammad, Alfian; Safarida, Nanda; Murdiah (Samarinda State Polytechnic, 2023)
The tourism sector can increase Regional Original Income, but its contribution has not been fully realized. Therefore, the government needs to play an important role in tourism development. This study aims to determine the tourism sector's contribution to Langsa City's Regional Original Income and the government's efforts related to tourism development. The research method employed a qualitative approach with a descriptive research type. The primary data for this study consisted of interview data, while the secondary data included documentation, tax reports, and Regional Original Income of Langsa City for the period 2018 to 2020. The study revealed that the tourism sector's contribution to the Regional Original Income of Langsa City from 2018 to 2020 was minimal. Specifically, Kota Forest and Mangrove Forest tourism contributed 0.0017%, Mutiara Water Park contributed 0.00004%, Virta Tirta Raya contributed 0.00029%, and Royal Waterboom contributed 0.00029%, resulting in a total contribution of 0.00232%. These figures indicate that the tourism sector's contribution to the city's income is very low. The Langsa City government is making efforts to develop tourism in a way that optimizes Regional Original Income through environmental improvement and structuring, sustainable use of natural resources, support for the local economy, and community involvement in maintaining existing tourist attractions in Langsa City.